Lusitanian amphorae - Vaz Pinto, Inês,; Almeida, Rui de,; Martin, Archer, (Roman and late antique Mediterranean pottery ;, 2016)
More than a century of archaeological investigation in Portugal has helped to discover, excavate and study many Lusitanian amphorae kiln sites, with their amphorae being widely distributed in Lusitania. These containers were identified in Ostia and Rome from the 1970s and thereafter in many sites around the Mediterranean, but their numbers have always seemed scarce. Were they not being recognized and therefore underestimated? Were they all fish-product amphorae? Did they ever reach a significant market share in the other provinces of Hispania? And what was their contribution to the supply of the city of Rome or to other cities in the centre of the Empire? This collective volume is a contribution to the discussion of these and other questions, and to a better understanding of the production and distribution of Lusitanian amphorae.